Lack of agency and sexual behaviors among married women: a study of population-based HIV impact assessment (PHIA) surveys in Malawi, Tanzania and Zambia - Roya Sherafat-Kazemzadeh; Gary Gaumer; William Crown; Elad Daniels; Jessica Brown; Fairooz Newaz; Allyala Nandakumar (Journal of Global Health Reports)
# Background Educational campaigns to prevent HIV/AIDS have shown mixed success in Africa. We hypothesized that women’s lack of agency in decision-making and taking discernible actions reduces the beneficial impact of HIV-related knowledge.